Spectrum of Quality of Life after Valve Surgery in Patients with Rheumatic Heart Disease. - Joshi, Dikshya; Shrestha, Anushruti; Gurung, Minani; Gautam, Navin C; Singh, Yogeshwor M.; Thakur, Apurba; Basnet, Nishes; Timala, Rabindra B. (Nepalese Heart Journal, 2021)
Background and Aims: Improvement in quality of life is one of the principal goals of valve surgery. The purpose of this study was to assess the quality of life in patients living with mechanical heart valves. Methods: We conducted a cross-sectional descriptive study among 131 (42 Males, and 89 Female) patients, who had undergone valve procedures at different times in clinic visit of department of cardiac surgery, unit I of Shahid Gangalal National Heart Centre from August 1 till August 29, 2019. Quality of life index was measured using Ferrans and Power quality of life index, cardiac version IV via written questionnaire or verbal interview. Results: Mean age was 40.57±1.4 (16-75) years. Mean duration of follow up was 4.68±4.03 years (3 months to 18 years). Subjects reported the lowest quality of life scores in the health and functioning domain prior to surgery (15.61±1.30), which improved 47.15% after surgery (22.95±0.45), psychological/spiritual domain improved 16.68%, social and economic domain 26.24%, family domain 11.49%, with overall improvement 28.62%. Women had significantly lower mean overall quality of life index (22.99±03.58) (95% confidence interval 22.24-23.75) compared to male counterparts (24.21±4.11) (95% confidence interval 22.92-25.49) (p<0.05). Family domain had the highest score at the latest follow up (28.84±1.63). There was a statistically significant correlation between the duration of operation and overall quality of life index (Pearson’s rho 0.217, p<0.01). There was no significant difference with the patients’ age. Conclusion: This study confers significant improvement of quality of life after valve surgery with time. Age does not appear to limit the quality of life. Family support seems to be the biggest strength in our population.